Estudo do potencial enzimático de micro-organismos endofíticos para a biotransformação de produtos naturais e análogos sintéticos - Silva, Bianca Ferreira da (Universidade Federal de São Carlos, 2009)
The endophytic microorganisms Penicillium griseoroseum, Penicillium brasilianum, Aspergillus flavus e Aspergillus aculeatus have shown to be very efficient in order to perform the most diferenciated biotransformation reactions. The fungi Penicillium griseoroseum has presented an elevated desmethylation selectivity of the caffeine substrate besides the desmethylation of the 2 ,4 ,6 - trimethoxyacetophenone. More complex chemical modifications as the formation of the C-C bond (in the flavanoid 5,7,3 ,4 ,5 -pentamethoxyflavanone) and chloration were also observed with this microorganisms. Yet when explored with flavonoids such as the naringenin and hesperetin, their respective chalcone and, with the glicosylated flavonoid the fungi has also shown itself active. Besides that, the oxidative capability of the Penicillium brasilianum e Aspergillus flavus fungi has been explored with the 1 indanone substrate. Both fungi have performed the Baeyer-Villiger oxidation reaction and the hidroxylation as well. Therefore, when testing glicosylated flavonoids with the fungi Aspergillus flavus their complete degradation was obtained, but with the respective methoxylated substrates no transformation has been obtained. The Aspergillus aculeatus fungi was explored concerning its capability of dimerizing substances. This way, the used substrates were the phenolics 2-naphthol, 1-naphthol e 1- naphthilamine compounds. As a biotransformation product a new reaction was obtained, a Fries rearrangement that has originated the adition of the ketil group to all tested substrates.
Study of endophitic microorganisms potential on the biotransformation of natural products
Keywords: Química orgânica; Biotransformação; Microorganismos endofíticos; Flavonoides; Oxigenases; CIENCIAS EXATAS E DA TERRA::QUIMICA